2019
DOI: 10.3347/kjp.2019.57.4.423
|View full text |Cite
|
Sign up to set email alerts
|

Coenurosis of Yak, Bos grunniens, caused by Taenia multiceps: A Case Report with Molecular Identification in Qinghai Tibetan Plateau Area, China

Abstract: Coenurosis is an important zoonotic helminthic disease caused by the larval stage of the tapeworm Taenia multiceps. This parasite typically infects the brain of the intermediate hosts, including sheep, goat, cattle and even humans. We report a case of T. multiceps infection in a yak confirmed by clinical symptoms, morphological characteristics, and molecular and phylogenetic analyses. The coenurus was thin-walled, whitish, and spherical in shape with a diameter of 10 cm. The parasite species was identified as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The disease has also been reported in animals other than small ruminants, including cattle [ 37 , 48 , 74 , 75 ], mouflon [ 76 , 77 ], buffalo, horses [ 78 , 79 ] and yak [ 80 , 81 ]. Coenurosis in rarely seen in the tissues of small ruminants other than those of the brain or spinal cord, and has been described mainly in Asian countries, and never in Europe or the Americas.…”
Section: Geographical Distribution and Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The disease has also been reported in animals other than small ruminants, including cattle [ 37 , 48 , 74 , 75 ], mouflon [ 76 , 77 ], buffalo, horses [ 78 , 79 ] and yak [ 80 , 81 ]. Coenurosis in rarely seen in the tissues of small ruminants other than those of the brain or spinal cord, and has been described mainly in Asian countries, and never in Europe or the Americas.…”
Section: Geographical Distribution and Epidemiologymentioning
confidence: 99%
“…Limited data have been published on the molecular characterization of T. multiceps in cattle, which mostly indicated similar genetic variants of T. multiceps to those found in sheep and goats [ 17 , 74 ]. Likewise, phylogenetic reconstructions based on 18S rRNA, cox1 and nad1 gene sequences showed that a T. multiceps yak isolate from China was closely related to T. multiceps isolates from other hosts and geographic locations [ 80 ].…”
Section: Molecular Characterizationmentioning
confidence: 99%
“…Moreover, C. cerebralis causes sheep coenurosis, which is common in Egypt, in which the metacestodes develop in the brain and spinal cord mainly, causing nervous signs, depression, circling, convulsions, head deviation, blindness, and ataxia leading to animals' death and severe economic DOI: https://dx.doi.org/10. 54203/scil.2022.wvj30 losses (Zhang, 2019). Dogs are a definitive host for Taenia species; a high incidence of infection by this metacestode in sheep should be reflected in humans in the same localities (Rostami et al, 2013).…”
Section: Introductionmentioning
confidence: 99%